2013
DOI: 10.1055/s-0032-1333275
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities of some Novel Benzhydrylpiperazine Derivatives

Abstract: This study presents the synthesis of nineteen 1-(substitutedbenzoyl)-4-benzhydrylpiperazine and 1-[(substitutedphenyl)sulfonyl]-4-benzhydrylpiperazine derivatives. In vitro cytotoxic activities of the compounds were screened against hepatocellular (HUH-7), breast (MCF-7) and colorectal (HCT-116) cancer cell lines by sulphorhodamine B assay. Among the test compounds, benzamide derivatives had high cytotoxic activity whereas sulfonamide derivatives showed variable 50% growth inhibition (GI50).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Recently studies had highlighted the anticancer potential of N-benzhydrylpiperazine and 1,3,4-oxadiazoles. Gurdal et al 18 had reported the cytotoxicity of N-benzhydrylpiper-azine derivatives against HUH-7, MCF-7 and HCT-116 cancer cell lines, however, the underlying cellular mechanism remained unexplored, likewise Zheng et al 35 had reported that oxadiazole derivatives induced apoptosis in MGC-803 cells. Lately, Zhao et al 36 showed that 1,3, 4-oxadiazole derivatives induced apoptosis in MDA-MB-231 but the mechanism remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently studies had highlighted the anticancer potential of N-benzhydrylpiperazine and 1,3,4-oxadiazoles. Gurdal et al 18 had reported the cytotoxicity of N-benzhydrylpiper-azine derivatives against HUH-7, MCF-7 and HCT-116 cancer cell lines, however, the underlying cellular mechanism remained unexplored, likewise Zheng et al 35 had reported that oxadiazole derivatives induced apoptosis in MGC-803 cells. Lately, Zhao et al 36 showed that 1,3, 4-oxadiazole derivatives induced apoptosis in MDA-MB-231 but the mechanism remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recently, N-benzhydrylpiperazines has gained much popularity by displaying anticancer activities. 18 Kumar et al 19 had reported the cytotoxicity of N-benzhydrylpiperazine containing sulfonyl chlorides, acid chlorides, and isothiocyanates derivatives toward various cancer cells. Similarly, Yarim et al 20 had also reported anticancer activities of benzoyl chloride derivatives containing N-benzhydrlypiperzines toward liver, breast, colon, gastric, and endometrial cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents caused induction of senescence-associated cell death through the inhibition of some kinase proteins 8 . In addition, Yarim and her co-workers previously reported various piperazine derivatives with high cytotoxic activity against liver (HUH-7, FOCUS, MAHLAVU, HepG-2, Hep-3B), breast (MCF-7, BT20 and T47D), colon (HCT-116), gastric (KATO-3), cervix (HeLa) and endometrial (MFE-296) cancer cell lines [9][10][11] . According to anticancer activity studies of benzothiazolepiperazine backbone, arylsulphonamides and arylthiol derivatives have potent cytotoxicity against a large scale of cancer cell lines such as breast (MCF-7), hepatocellular (HepG-2), prostate (DU-145) cancers and CD4 + human acute T-lymphoblastic leukaemia (CCRF-CEM) 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Yarim et al, also performed cytotoxicity screenings for some 4-chlorobenzhydrylpiperazines substituted with variable benzoyl chloride derivatives and reported their high activities against liver (HUH-7, FOCUS, MAHLAVU, HepG-2, Hep-3B), breast (MCF-7, BT20, T47D, CAMA-1), colon (HCT-116), gastric (KATO-3) and endometrial (MFE-296) cancer cell lines 45 . In addition, our work group has recently reported a study in which sulfonamide and benzamide derivatives of benzhydrylpiperazines were discussed for their cytotoxicities against HUH-7, MCF-7 and HCT-116 cancer cell lines 52 .…”
Section: Introductionmentioning
confidence: 99%